Interaction of client—the scaffold on which FeS clusters are build—with J-domain protein Hsc20 and its evolving Hsp70 partners - Marszalek, Jaroslaw; Craig, Elizabeth A. (Frontiers in Molecular Biosciences, 2022)
In cells molecular chaperone systems consisting of Hsp70 and its obligatory J-domain protein (JDP) co-chaperones transiently interact with a myriad of client proteins—with JDPs typically recruiting their partner Hsp70 to interact with particular clients. The fundamentals of this cyclical interactions between JDP/Hsp70 systems and clients are well established. Much less is known about other aspects of JDP/Hsp70 system function, including how such systems evolved over time. Here we discuss the JDP/Hsp70 system involved in the biogenesis of iron-sulfur (FeS) clusters. Interaction between the client protein, the scaffold on which clusters are built, and its specialized JDP Hsc20 has stayed constant. However, the system’s Hsp70 has changed at least twice. In some species Hsc20’s Hsp70 partner interacts only with the scaffold, in others it has many JDP partners in addition to Hsc20 and interacts with many client proteins. Analysis of this switching of Hsp70 partners has provided insight into the insulation of JDP/Hsp70 systems from one another that can occur when more than one Hsp70 is present in a cellular compartment, as well as how competition among JDPs is balanced when an Hsp70 partner is shared amongst a number of JDPs. Of particularly broad relevance, even though the scaffold’s interactions with Hsc20 and Hsp70 are functionally critical for the biogenesis of FeS cluster-containing proteins, it is the modulation of the Hsc20-Hsp70 interaction per se that allows Hsc20 to function with such different Hsp70 partners.